Problems Related to Reintegration of Young Ex-Offenders in Estonia - Markina, Anna (Kriminologijos studijos, 2019)
Based on 22 semi-structured interviews with 24 young ex-offenders in Estonia, this article looks at the effect that stigmatization has on the reintegration of young ex-offenders. The study looks at to what extent and in which domains ex-offenders experience stigma, how they manage it, and what effect it has on social participation and involvement. The results indicate that young ex-offenders experience stigma while looking for jobs and accommodation and when interacting with the criminal justice system. The strategies for managing stigma mostly include secrecy and withdrawal. These strategies are closely related to self-stigmatization, low societal participation, and a low level of trust toward state institutions.